INTERNAL RESOURCES AND INTERNATIONAL ENTRY STRATEGIES The serviced apartment context - Hämäläinen, Juha (My University, 2017)
The research focuses on international entry strategies and key resources in the serviced apartment context. The industry is currently the fastest growing segment in the accommodation sector. Companies apply highly varied strategical approaches and prioritize their resources in very different ways. The study provides useful insight into the structure of the serviced apartment industry and presents an interesting decision making framework for the strategic leaders. The topic of the research is Internal resources and international entry strategies in the serviced apartment context. The research answers to following questions: Which international entry strategies are applied in the serviced apartment industry in Europe and globally? What are the key resources in the serviced apartment industry and how do they create a competitive advantage for the firms in the business? What is an optimal resource - entry mode bundle for a company from a competitive advantage perspective? The theoretical approach of the research consists of the international entry strategy literature combined with the resource based view and Jay Barney’s classification of resources to valuable, rare, inimitable and non-substitutable ones. The main purpose is to find the resource – strategy –bundles which build competitive advantage for a firm. The resource organization –concept is a key element in the research to define these bundles. The transaction cost theory is also described shortly to understand better which assets are specific for a firm and how these are connected to international entry strategies. The research has an empirical qualitative approach with an inductive perspective. The chosen method helps to understand how the emerging industry functions to acquire necessary preunderstanding for the future quantitative analysis. The research material consists of 12 interviews with international decision makers in the industry. The interviews are complemented with eight short discussions with other industry professionals in different industry events. The applied entry strategies are diverse in the sector. The companies have successfully used such traditional strategies as management contracts and lease agreements but also such emerging strategies as mixed lease agreements at different commitment levels and licensing as a quick expansion strategy mode. Commitment and control levels do not necessarily increase or decrease hand in hand along with a strategy mode change as traditionally presented in the literature. The participants prioritized following resources above other: company’s employees, a high quality customer service process, sales and marketing competence, an existing customer base, a company’s brand, real estate owner relationships, revenue management competence, a functional reservation system and a company’s culture. The resources with most intangible elements are often the differentiating factors in the markets. Interestingly, many companies have also developed complex history dependent interconnected assets, such as a history in the real estate investments or in the hotel industry. This background provides a competitive benefit in the markets. An important academic conclusion is that traditional theoretical concepts explain well modern environment when combined with each other to provide more explanatory framework than one concept would provide alone. Additionally, concepts need to be adjusted to specific research contexts which are often distinctive and dynamic. From the managerial perspective, the companies with active client following approach had the highest potential to increase their competitive advantage by streamlining their resources to fit their strategic choices. The real estate focused companies had already well organized resource – strategy bundles.

Tutkielma keskittyy kansainvälistymisstrategioihin ja ydinresursseihin huoneistomajoituksen toimialalla. Toimiala on tällä hetkellä majoitusalan nopeimmin kasvava sektori. Yritykset käyttävät hyvin erilaisia strategioita ja priorisoivat resurssejaan monin eri tavoin. Tutkimus tarjoaa mielenkiintoisen näkökulman toimialan rakenteeseen ja ehdottaa strategista päätöksentekomallia alan johtajille. Tutkimuksen aihe on Sisäisen resurssit ja kansainväliset markkina-avausstrategiat huoneistomajoituksen kontekstissa. Tutkimus vastaa seuraaviin kysymyksiin: Mitä kansainvälistymisstrategioita käytetään huoneistomajoituksen toimialalla Euroopassa ja globaalisti? Mitkä ovat ydinresurssit huoneistomajoituksen toimialalla ja miten nämä luovat kilpailuetua yrityksille? Mikä on optimaalinen resurssi – kansainvälistymisstrategia – yhdistelmä yritykselle kilpailuedun näkökulmasta? Tutkimuksen teoreettinen lähestymistapa muodostuu kansainvälistymisstrategioiden kirjallisuudesta yhdistettynä resurssi perusteiseen näkökulmaan sekä Jay Barneyn luokitteluun arvokkaisiin, harvinaisiin, ei – kopioitaviin ja korvaamattomiin resursseihin. Tarkoituksena on löytää resurssi-strategia – yhdistelmiä, jotka luovat kilpailuetua yritykselle. Resurssien organisointi – konsepti on yksi ydinelementti tutkimuksessa, jonka avulla määritetään näitä yhdistelmiä. Transaktiokustannusteoria kuvataan myös lyhyesti, jotta ymmärretään paremmin, mitkä resurssit ovat erityisiä yritykselle ja miten nämä ovat yhteydessä kansainvälistymisstrategioihin. Tutkimuksen lähestymistapa on empiirinen ja kvalitatiivinen induktiivisella näkökulmalla. Valittu metodi edesauttaa ymmärtämään miten kasvava toimiala rakentuu, jotta saavutetaan riittävä esiymmärrys tulevaisuuden kvantitatiiviselle analyysille. Tutkimusmateriaali koostuu 12:sta kansainvälisen päättäjän haastattelusta, joista osaa haastateltiin kahteen kertaan. Haastatteluja on täydennetty kahdeksalla lyhyellä keskustelulla eri ammattilaisten kanssa toimialan eri tapahtumissa. Kansainvälistymisstrategiat ovat hyvin erilaisia toimialalla. Yritykset ovat menestyksekkäästi käyttäneet perinteisiä strategioita, kuten johtamissopimuksia ja vuokrasopimuksia mutta myös uusia strategioita, kuten muuttuva vuokra – sopimus tai lisensointi nopean kasvun strategiana. Investoinnin ja kontrollin taso ei välttämättä lisäänny tai vähene käsi kädessä strategiamuodon vaihtuessa kuten kirjallisuudessa on perinteisesti esitetty. Osanottajat pitivät tärkeinä seuraavia resursseja: yrityksen työntekijät, laadukas asiakaspalveluprosessi, myynti- ja markkinointiosaaminen, olemassa olevat asiakkuudet, yrityksen brändi, kiinteistöomistajasuhteet, tuottojohtamisosaaminen, toimiva varausjärjestelmä ja yrityksen kulttuuri. Resurssit, joissa on eniten aineettomia elementtejä, ovat usein eniten yrityksiä toisistaan erottavia tekijöitä. Mielenkiintoista oli havaita, että monet yritykset ovat myös kehittäneet monimutkaisia historiaan ja toisiinsa sidoksissa olevia resursseja toiselta toimialalta kuten historia kiinteistösijoitus- tai hotellialalla. Tämä tausta luo kilpailuetua yrityksille. Tärkeä tieteellinen johtopäätös tutkimuksessa oli se, että perinteiset teoreettiset konseptit selittävät hyvin modernia ympäristöä kun niitä yhdistetään toisiinsa, jolloin konseptien yhdistelmä selittää paremmin ilmiötä kuin konseptit erillään. Lisäksi konseptit tulee sopeuttaa tutkimuskontekstiin, jotka ovat usein erilaisia ja muuttuvia. Johtamisen näkökulmasta niillä yrityksillä, joilla on toimintatapana asiakkaan aktiivinen seuraaminen, on myös suurin potentiaali lisätä kilpailuetuaan virtaviivaistamalla resurssejaan paremmin strategiavalintaan soveltuvaksi. Kiinteistöihin keskittyvillä yrityksillä resurssit on jo valmiiksi paremmin järjestetty tukemaan strategiaa.